The comparative analysis of the compressible plasma streams generated in QSPA from the various gases - Kozlov, A.N.; Drukarenko, S.P.; Seytkhalilova, E.I.; Solyakov, D.G.; Velichkin, M.A. (Вопросы атомной науки и техники, 2012)
The numerical research of streams dynamics in the channel and the compressible flows at the QSPA output is carried out for the plasma generated from hydrogen, helium, argon and xenon. The MHD equations in the one-fluid approach taking into account the final conductivity of medium, the heat conductivity and the effective losses of radiation energy underlie the numerical model of the two-dimensional axisymmetric plasma flows. Features of the compressible plasma streams generated from various gases are revealed. Проведено численное исследование динамики потоков в канале и компрессионных течений на выходе из КСПУ для плазмы, генерируемой из водорода, гелия, аргона и ксенона. В основе численной модели двумерных осесимметричных течений плазмы лежат МГД-уравнения в одножидкостном приближении с учетом конечной проводимости среды, теплопроводности и эффективных потерь энергии на излучение. Выявлены особенности компрессионных потоков плазмы генерируемой из различных газов. Проведено чисельне дослідження динаміки потоків в каналі і компресійних течій на виході з КСПУ для плазми, яка генерується з водню, гелію, аргону і ксенону. В основі чисельної моделі двовимірних осесиметричних течій плазми лежать МГД-рівняння в однорідинному наближенні з урахуванням кінцевої провідності середовища, теплопровідності і ефективних витрат енергії на випромінювання. Виявлено особливості компресійних потоків плазми, які генерується з різних газів.